2014
DOI: 10.1111/1751-7915.12178
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the food production chain from farm practices to vegetable processing on outbreak incidence

Abstract: The popularity in the consumption of fresh and fresh-cut vegetables continues to increase globally. Fresh vegetables are an integral part of a healthy diet, providing vitamins, minerals, antioxidants and other health-promoting compounds. The diversity of fresh vegetables and packaging formats (spring mix in clamshell container, bagged heads of lettuce) support increased consumption. Unfortunately, vegetable production and processing practices are not sufficient to ensure complete microbial safety. This review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
111
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(112 citation statements)
references
References 77 publications
(94 reference statements)
0
111
0
1
Order By: Relevance
“…Immediately following treatment by FAC, unencapsulated or nanoparticle-entrapped geraniol, Escherichia coli O157:H7 and Salmonella counts on spinach ranged from 1.5 to 6.1 log10 CFU/cm 2 . Geraniol-loaded nanoparticles reduced pathogens to non-detectable numbers (detection limit: 0.5 log10 CFU/cm 2 ) on refrigerated and moderately temperature-abused samples (15°C) within 7 days of storage posttreatment, and Microbial pathogens have been associated with a variety of produce-borne human disease outbreaks, with an apparent increase in the frequency of outbreaks in recent years (CDC, 2012a,b;Gould et al, 2013;Slayton et al, 2013;Jung et al, 2014;Angelo et al, 2015). Painter et al (2013) reported leafy green produce commodities were the most frequently implicated pathogen transmission vehicles in US human foodborne disease cases, as well as the food vehicle type second most frequently linked to hospitalizations resulting from foodborne disease.…”
mentioning
confidence: 99%
“…Immediately following treatment by FAC, unencapsulated or nanoparticle-entrapped geraniol, Escherichia coli O157:H7 and Salmonella counts on spinach ranged from 1.5 to 6.1 log10 CFU/cm 2 . Geraniol-loaded nanoparticles reduced pathogens to non-detectable numbers (detection limit: 0.5 log10 CFU/cm 2 ) on refrigerated and moderately temperature-abused samples (15°C) within 7 days of storage posttreatment, and Microbial pathogens have been associated with a variety of produce-borne human disease outbreaks, with an apparent increase in the frequency of outbreaks in recent years (CDC, 2012a,b;Gould et al, 2013;Slayton et al, 2013;Jung et al, 2014;Angelo et al, 2015). Painter et al (2013) reported leafy green produce commodities were the most frequently implicated pathogen transmission vehicles in US human foodborne disease cases, as well as the food vehicle type second most frequently linked to hospitalizations resulting from foodborne disease.…”
mentioning
confidence: 99%
“…Although there is no established criteria for concentration of E. coli in the raw leafy vegetables (ICMSF, 1986), concentration of E. coli >3 log cfu/g observed in this study may pose health risks to consumers. This was expected, because Jung et al, 2014). However, Chinese cabbage which has a natural epiphytic flora, it may acquire contamination from various incidental and accidental inputs.…”
Section: Resultsmentioning
confidence: 95%
“…The potential sources of pathogen contamination during preharvest practices may include dust, soil, polluted irrigation water and rodents (Jung et al, 2014). Previous studies conducted on leafy vegetables in Ghana (Keraita et al, 2007) and in Pakistan (Ensink et al, 2007) during pre-and post-harvest handling practices reported faecal pathogens contamination.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of sewage contaminated water in the food production chain can lead to emergence of water borne diseases particularly by pathogens of public health importance (Jung et al, 2014).…”
mentioning
confidence: 99%